Mortality Risk Assessment of Total Knee Arthroplasty and Related Surgery After Percutaneous Coronary Intervention - Von Keudell, Arvind G. (Open Orthop J, 2016)
BACKGROUND: The optimal antiplatelet therapy (APT) treatment strategy after Coronary Artery Stenting (CAS) in non-cardiac surgery, such as total knee arthroplasty (TKA) or urgent TKA-related surgery remains unknown. METHODS: We built a decision tree model to examine the mortality outcomes of two alternative strategies for APT after CAS use in the perioperative period namely, continuous use and discontinuation. RESULTS: If surgery was performed in the first month after CAS placement, discontinuing APT led to an estimated 30-day post TKA mortality of 10.5%, compared to 1.0% in a strategy with continuous APT use. Mortality with both strategies decreased with longer intervals. CONCLUSION: Our model demonstrated that APT discontinuation in patients undergoing TKA or urgent TKA related surgery after CAS placement might lead to greater 30-day mortality up to one year.